2017
DOI: 10.1093/jamia/ocx021
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of patient-provider secure messaging at two Veterans Health Administration medical centers: message content and resolution through secure messaging

Abstract: The majority of messages were transactional and initiated by patients or caregivers. Not all content categories were fully addressed over SM. Further education and training for both patients and clinical teams could improve the quality and efficiency of SM communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 33 publications
10
37
2
Order By: Relevance
“…Our analysis revealed that the majority of patient secure messages included logistical content, demonstrating the organizing efforts of patients to ensure that they had the resources (eg, prescriptions) needed for their own care. These findings are consistent with previous studies, including some studies conducted in VA, highlighting the frequent use of email and secure messaging by patients to address administrative issues and related care actions [ 29 , 41 , 42 , 44 - 46 ]. Although there may be a tendency to view such content as uncomplicated or routine, we believe that it underscores the importance of secure messaging as a tool that patients use to promote care coordination.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our analysis revealed that the majority of patient secure messages included logistical content, demonstrating the organizing efforts of patients to ensure that they had the resources (eg, prescriptions) needed for their own care. These findings are consistent with previous studies, including some studies conducted in VA, highlighting the frequent use of email and secure messaging by patients to address administrative issues and related care actions [ 29 , 41 , 42 , 44 - 46 ]. Although there may be a tendency to view such content as uncomplicated or routine, we believe that it underscores the importance of secure messaging as a tool that patients use to promote care coordination.…”
Section: Discussionsupporting
confidence: 92%
“…Nearly half of the patient messages in our sample were coded as information updates, in which they informed health care team members about some aspect of their health. Patient provision of such updates has been documented in previous studies [ 42 , 44 , 46 ] and is a powerful illustration of how secure messaging can facilitate the shift from episodic to continuous care and cultivate ongoing, healing relationships as argued for by the Institute of Medicine [ 60 ]. In addition to providing updates, patients also used secure messaging to seek information about a variety of topics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we noted in the introduction, the purpose of this paper was three-fold. First, we sought to present basic measurements of usage that are similar to other studies found in the literature [25][26][27][28]. In so doing, we hope to foster both a greater understanding of usage and open conversations about similarities with ambulatory portals.…”
Section: Discussionmentioning
confidence: 95%
“…29 In another study, Shimada et al coded secure messages sent to primary care providers via an outpatient portal and found that they were most frequently transactional in nature, involving requests for medication refills and questions about scheduling. 30 However, needs specific to hospitalized patients may be appreciably different in this context and merely providing portal functions in the inpatient environment similar to those available in outpatient settings may be insufficient. Hospitalization may serve as a cue to action, increasing the patient's focus on their health and potentially increasing their willingness to use a portal to engage in their care.…”
Section: Background and Significancementioning
confidence: 99%